Pelatihan Pengenalan Sofware Edukasi Untuk Siswi SMP ISLAM TERPADU SABBIHISMA Padang - Sutiyem; Suhery; Deni Suwandhani; Riza Yonita; Thesa Alif Ravelby (AMMA : Jurnal Pengabdian Masyarakat, 2022)
SABBIHISMA INTEGRATED ISLAMIC SMP, Padang City, is one of the choices for junior high schools in Padang City. The use of software as a source and medium of school learning in the future The COVID-19 pandemic is very important. The objectives to be achieved from this educational software introduction training are: Introducing training participants to the importance of Mastering Information Technology and Computers today and teaching how to use Microsoft Word, MS. Excel, Power Point which can be used to learn typing and others. The method used in this activity is Education to the Community in the form of lectures and training on introductions basic computer and application Microsoft Word, MS. Excel, Powerpoint. The result of this activity is to provide implications for adding participants' insight into Microsoft Word, MS. Excel, Powerpoint. In view of the educational activities that during the covid-19 pandemic were carried out regularly, online/online has made many limitations for school-age children in developing skills, especially the practice of using computers. This can be seen from the results of the evaluation that carried out before and after the training activities. Where there is improvement understanding and knowledge before and after the implementation of the activity. Keywords: Miscrosoft Word, MS. Excel, Power Point, covid-19